Inhibition and activation systems of behavior and suicide mediating role of cognitive emotion regulation - Soudabeh Ershadi Manesh (Shahid Beheshti University of Medical Sciences, 2024)
Background: This study aimed to predict suicide attempts based on behavioral activation and inhibition systems (BAS/BIS) with the mediating role of cognitive emotion regulation (CER) strategies among adolescents of Abyek City. Methods: The research methodology was descriptive-correlational. The cluster sampling method was used, and the resulting sample included 194 adolescents who responded to the BAS/BIS questionnaire (Carver & White, 1994), CER questionnaire, and Beck scale for suicide ideation. Path analysis was employed to evaluate the proposed model using AMOS 24.0 and SPSS 27 software. Results: The findings indicate that the proposed model is fitted with the data well. The results of path analysis showed that the BAS/BIS systems explain 27% of the variance of maladaptive CER and 61% of the variance of adaptive CER. In addition, maladaptive CER, BAS, and BIS explain 65% of the variance of suicide attempts. Conclusion: Low levels of BAS, high levels of BIS, and the use of maladaptive CER skills can be considered risk factors for suicide attempts in adolescents.